Stress-Hormone Dynamics and Working Memory in Healthy Women Who Use Oral Contraceptives Versus Non-Users - Høgsted, Emma Sofie; Borgsted, Camilla; Dam, Vibeke H.; Nasser, Arafat; Rye Jørgensen, Niklas; Ozenne, Brice; Stenbæk, Dea Siggaard; Frokjaer, Vibe G. (Frontiers in Endocrinology, 2021)
Background Women who use oral contraceptives (OCs) may have a higher risk of developing a depression, which is associated with both vulnerability to stress and cognitive dysfunction. OCs disrupt the hypothalamic-pituitary-gonadal (HPG) axis by suppressing endogenous sex steroid production including estradiol. The HPG axis and the hypothalamic-pituitary-adrenal (HPA) axis are known to interact, possibly through modulations driven by estradiol. OCs may affect HPA regulation capacity, i.e., disturb cortisol dynamics such as the cortisol awakening response (CAR), and influence cognition such as working memory (WM). We hypothesize that OC use is associated with blunted cortisol dynamics and impaired WM performance relative to non-users. Methods Data from 78 healthy women in the reproductive age were available from the CIMBI database. We evaluated if CAR and WM differed between OC users (n=25) and non-users (n=53) and if the level of estradiol modulated the OC use effect on CAR or WM in generalized least square models. Results We found that OC users had a blunted CAR (p= 0.006) corresponding to a 61% reduction relative to non-users; however, no estradiol-BY-OC use interaction effect was observed on CAR. Also, OC users had higher cortisol levels at awakening compared to non-users (p = 0.03). We observed no effect of OC use or an estradiol-BY-OC use interaction effect on WM. Also, within the OC user group, neither CAR nor WM was associated with suppressed estradiol. CAR was not associated with WM. Conclusion Healthy women who use OCs have blunted cortisol dynamics relative to non-users. However, we could not detect OC use effects on working memory in our sample size. We speculate that disrupted cortisol dynamics may be important for the emergence of depressive symptoms in OC users.